Field evaluation of sorghum varieties to Striga hermonthica infestation in north eastern Nigerian savannas - Dugje, I.Y.; Ekeleme, F.; Kamara, A.Y.; Menkir, A.; Chikoye, David; Omoigui, L.O. (2010)
Striga hermonthica parasitism is a major constraint limiting Sorghum productivity in the Nigerian savanna. Field experiments were conducted in 2005 and 2006 rainy seasons to evaluate the response of sorghum varieties to striga infestation. A randomised complete block design was used to screen 12 sorghum varieties comprising 10 exotic varieties from Purdue University, USA: (P9401, P9402, P9403, P9404, P9405, P9406, P9407, P9408, PSL985061, SRN39), and KSV 8, and Hanungiwa (local checks) replicated three times in striga sick field in Nzuda (Sudan savanna) and Wandali (Northern Guinea savanna). Emerged striga plants m-2 was significantly higher at Wandali than Nzuda. However, significantly lower values were observed for the exotic varieties than KSV 8 or Hanungiwa; and slightly lower values were observed for PSL985061 and P9402 among the exotic ones. Grain yield ha-1 and fodder yield ha-1 were each significantly higher at Wandali than Nzuda in 2005, but the reverse was observed in 2006. Grain yield was significantly higher for PSL985061, KSV 8, and P9401, respectively, across both locations and years, while P9402, P9405 and KSV 8 significantly produced superior fodder yield. The results further confirm previous studies that suggest tolerance of KSV 8, and resistance of PSL985061, P9401 and P9402 to striga hermonthica.